2001
DOI: 10.1046/j.1365-2168.2001.01655.x
|View full text |Cite
|
Sign up to set email alerts
|

One-year survey of carcinoma of the oesophagus and stomach in Wales

Abstract: Tumour resection conferred a survival advantage. Wider use of laparoscopy is advocated. Improved selection for surgery should result in a lower mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
32
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 34 publications
7
32
0
Order By: Relevance
“…In 1995, an audit of all cases diagnosed with oesophagogastric cancer in Wales found the incidence of oesophageal cancer to be 11/ 100 000 (Pye et al, 2001). Based upon this data, Velindre Cancer Centre serving South East Wales with a population of 1.48 million people would expect to see 165 patients per year with this disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1995, an audit of all cases diagnosed with oesophagogastric cancer in Wales found the incidence of oesophageal cancer to be 11/ 100 000 (Pye et al, 2001). Based upon this data, Velindre Cancer Centre serving South East Wales with a population of 1.48 million people would expect to see 165 patients per year with this disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite better staging and improving perioperative care, the outcome from this treatment remains poor, with 30 -45% patients surviving 2 years after radical resection (Kelsen et al, 1998;Medical Research Council Oesophageal Cancer Working Group, 2002). The proportion of patients for whom this treatment is selected varies in different countries from 25 to 45% (Fok et al, 1994;Coia et al, 2000;Pye et al, 2001). This complex surgery is challenging for both the surgeon and the patient; between 5 and 10% will die as a result of an oesophagectomy and 30 -40% will suffer significant postoperative morbidity.…”
mentioning
confidence: 99%
“…Thorough and accurate staging of patients is of paramount importance in the selection of patients for whom surgery could be potentially curative [4].The recent large regional audit of esophagogastric cancer in Wales revealed that many surgeons continue to undertake small caseloads; staging laparoscopy was performed in 16% of cases; and no fewer than 23% of patients underwent open-and-close operations [3]. Staging protocols for patients with gastric cancer vary, not only from hospital to hospital within the United Kingdom, but from east to west worldwide.…”
mentioning
confidence: 99%
“…Despite the introduction of open access gastroscopy, as many as one in three British patients continue to present with advanced disease that is incurable by means of surgery [2,3]. Thorough and accurate staging of patients is of paramount importance in the selection of patients for whom surgery could be potentially curative [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation